Extraction of Ethyl-p-methoxycinnamate from Kaempferia galanga L. - Trong Bien, Tran; Quang Trung, Ngo; Van Han, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 4, 2020)
In this study, ethyl- p -methoxycinnamate (EPMC) was extracted from Kaempferia galanga L. by different methods. The study results show that vacuum drying process led to a significant decrease in EPMC content in the herb (about 7%); EPMC obtained by water distillation not only had a high purity and yield but could also be applied for both fresh and dried herb; whereas, Soxhlet extraction with n -hexane solvent brought the highest extraction yield (1.99% on dried herb weight) despite lower purity when compared to that by water distillation method. Keywords Ethyl- p -methoxycinnamate, EPMC, Kaempferia galanga L., extraction. References [1] Botany Department, Botany, Hanoi University of Pharmacy, 2005 (In Vietnamese). [2] A. Kumar, Phytochemistry, pharmacological activities and uses of Indian traditional medicinal plant Kaempferia galanga L. – An overview, Journal of Ethnopharmacology (2020) 112667. https://doi.org/10.1016/j.jep.2020.112667. [3] H.J. Ko, H.J. Kim, S.Y. Kim, H.Y. Yun, K.J. Baek, N.S. Kwon, W.K. Whang, H.R. Choi, K.C. Park, D.S. Kim, Hypopigmentary Effects of Ethyl P‐Methoxycinnamate Isolated from Kaempferia galanga, Phytotherapy research 28(2) (2014) 274-279. https://doi.org/10.1002/ptr.4995. [4] M. Bonesi, J. Xiao, R. Tundis, F. Aiello, V. Sicari, M. R. Loizzo, Advances in the Tyrosinase Inhibitors from Plant Source, Current Medicinal Chemistry 26(18) (2019) 3279-3299. https://doi.org/10.2174/0929867325666180522091311. [5] M.I. Umar, M.Z. Asmawi, A. Sadikun, A.M. Majid, F.S. Al-Suede, L.E. Hassan, R. Altaf, M.B. Ahamed, Ethyl-p-methoxycinnamate isolated from Kaempferia galanga inhibits inflammation by suppressing interleukin-1, tumor necrosis factor-α, and angiogenesis by blocking endothelial functions, Clinics 69(2) (2014) 134-144. https://doi.org/10.6061/clinics/2014(02)10. [6] D. Lakshmanan, J. Werngren, L. Jose, K.P. Suja, M.S. Nair, R.L. Varma, S. Mundayoor, S. Hoffner, R.A. Kumar, Ethyl p-methoxycinnamate isolated from a traditional anti-tuberculosis medicinal herb inhibits drug resistant strains of Mycobacterium tuberculosis in vitro, Fitoterapia 82(5) (2011) 756-761. https://doi.org/10.1016/j.fitote.2011.03.006. [7] W. Sirisangtragul, B. Sripanidkulchai, Effects of Kaempferia galanga L. and ethyl-p-methoxycinnamate (EPMC) on hepatic microsomal cytochrome P450s enzyme activities in mice, J. Sci. Technol. 33(4) (2011) 411-417. [8] J. Wu, F. Ge, D. Wang, X. Xu, Combination of supercritical fluid extraction with high-speed countercurrent chromatography for extraction and isolation of ethyl p -methoxycinnamate and ethyl cinnamate from Kaempferia galanga L., Separation Science and Technology 51(10) (2016) 1757-1764. https://doi.org/10.1080/01496395.2016.1176046. [9] N. Srivastava, Ranjana, S. Singh, A.C. Gupta, K. Shanker, D.U. Bawankule, S. Luqman, Aromatic ginger (Kaempferia galanga L.) extracts with ameliorative and protective potential as a functional food, beyond its flavor and nutritional benefits, Toxicol Rep 6 (2019) 521-528. https://doi.org/10.1016/j.toxrep.2019.05.014. [10] I. Komalaa, Supandia, Nurhasnib, O.S. Bethaa, Yardia, S. Mufidaha, M. Rezaa, M.S. Alia, N.S. Auliaa, Sutara, Microwave Assisted Synthesis of p-Methoxycinnamamides and p-Methoxy-β-nitrostyrenes from Ethyl p-methoxycinnamate and Screening their Anti-inflammatory Activity, Natural Product Communications 12(8) (2017) 1265-1268. [11] Vietnamese Pharmacopoeia, the 5th edition, Appendix 2, (2017) (In Vietnamese) [12] AOAC International, AOAC official methods of analysis, Appendix K: Guidelines for Dietary Supplements and Botanicals, 2013. [13] P. Lunger, M. Weber, N. X. Dung, N. T. B. Tuyet, Ethyl p-Methoxycinnamate from Kaempferia galanga L. in Vietnam, Acta Cryst C52 (1996) 1255-1257. https://doi.org/10.1107/S0108270195016027. [14] S.K. Gupta, A.B. Banerjee, Achari B., Isolation of Ethyl p-methoxycinnamate, the major antifungal principle of Curcumba zedoaria, Curcumba zedoaria. Lloydia 39(4) (1976) 218-222. [15] M.I. Umar, M.Z. Asmawi, A. Sadikun, I.J. Atangwho, M.F. Yam, R. Altaf, A. Ahmed, Bioactivity-guided isolation of ethyl-p-methoxycinnamate, an anti-inflammatory constituent, from Kaempferia galanga L. extracts, Molecules 17(7) (2012) 8720-34. https://doi.org/10.3390/molecules17078720.